Nomadak Tx - Fuente, Raúl de la (Spain : Otxoa, Igor, 2006)
Henry Wadsworth Longfellow once famously remarked, “Music is the universal language of mankind,” and perhaps nowhere is this sentiment felt more strongly than in this jubilant film about two musicians who journey to some of the most remote regions of the world, using the traditional Basque musical instrument, the txalaparta, as a medium for cross-cultural exchange and understanding. The txalaparta is a traditional Basque instrument (similar to a xylophone) that was originally a communication device between Basque tribes. In this spirit of communication, Igor Otxoa and Harkaitz Martínez have a dream to turn the txalaparta into a meetingplace—not only for people, but for different cultures as well. This wish leads them to make a trip in search of the world’s last remaining nomadic tribes. From the north of India to the Mongolian Steppes, from the Sahara desert to Lapland, the film captures an extraordinarily fluent and dynamic conversation across borders and languages, articulated through music. Through encounters with other musicians—a Mongol musician and a Hindu taxi driver, a Sami singer and an aging Saharan lady—the txalaparta becomes more than a musical instrument; it is a tool for communication in which everyone expresses their desires. Stunning photography and superb music fill nearly every frame of the film, culminating in an amazing performance piece involving the music of all tribes in unison with the txalaparta. With little dialogue, the film speaks volumes on the significance of music in our lives, and its power to connect people all over the world.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films